Entre el currículum y la disciplina, la crítica - DULUC, Silvia (UNIVERSIDAD NACIONAL DE ENTRE RIOS, 2004)
BAUDINO, SILVINA; GIACAGLIA, MIRTA ARTEMIA; CANDIOTI DE DE ZAN, MARIA ELENA; RATTERO, CARINA; VITTORI, ANDREA